Sim Good Reception: utveckling av plattformsoberoende mobilapplikation - Hermansson, Erik; Spetz, Olof (My University, 2015)
Apper Systems is a IT consultant company which focuses on administrative system development. One of their software products is Supply Integration Manager (SIM). SIM is used for communication between suppliers and customers. A part of the delivery process is the recieving of goods. This is done with the use of scanning units. Scanning units require maintenance and can be expensive. The purpose of this project was to develop a cross-plattform mobile application which can be an alternative to scanning units and integrate with SIM. With cross-platform development a single application can reach multiple platforms. This streamlines the work process but there are many different developement alternatives and it can be hard to choose. A short evaluation of development alternatives was performed to determine how the application would be developed. The application was developed using web technologies such as HTML, CSS and JavaScript. It has the following supported platforms: Android, iOS and Windows Phone 8. This thesis report describes the performed evalution and the development of the application. The resulting evaluation compared six different solutions, one of these were chosen to develop the application. The resulting application works in accordance to the requirements. This report is written in Swedish.
Keywords: Data- och informationsvetenskap; Computer and Information Science